Podstawy teorii pełzania ustrojów hiperstatycznych wstępnie sprężonych - EIMER, Czesław (Engineering Transactions, 1957)
The foundations of the theory of creep of statically indeterminate prestressed structuresDealt with in this paper Pare the foundations of a general theory of creep in statically indeterminate prestressed structures, in particular the derivation of systems of equations enabling the determination of the redundant quantities as functions of time; a general discussion of methods for solving such equations is included.The considerations are based on the Volterra-Boltzmann general theory of linear creep, leading to systems of linear equations [see the system (2.21)].On the basis of accurate solutions, consideration is given to the principal ways in which the theory can be simplified. These ways are: simplification of the equations of internal statical indeterminacy (in the case of concentrated reinforcement); simplification of the equations of external statical indeterminacy (continuous beams); transition to a homogeneous system (together with the case of prestressing reinforcement allowed to slide in its channels); and replacement of integral equations by differential equations. No practical examples are solved in this investigation. They will constitute the subject of a separate paper.